Emerging antifungal resistance in Trichophyton mentagrophytes: insights from susceptibility profiling and genetic mutation analysis - Yakun Shao; Jin Shao; Sybren de Hoog; Paul Verweij; Lin Bai; Riina Richardson; Malcolm Richardson; Zhe Wan; Ruoyu Li; Jin Yu; Yinggai Song (Emerging Microbes and Infections)
Trichophyton species, the leading cause of dermatophytosis globally, are increasingly resistant to antifungal treatments, concerns about effective management strategies. In light of the absence of established resistance criteria for terbinafine and azoles, coupled with a dearth of research on resistance mechanisms in Trichophyton, antifungal susceptibility and drug resistance gene diversity were analyzed across 64 T. mentagrophytes, 65 T. interdigitale, and 2 T. indotineae isolates collected in China between 1999 and 2024 and 101 published T. indotineae strains. Analyses of the minimum inhibitory concentrations (MICs) of terbinafine, itraconazole, voriconazole, posaconazole, and isavuconazole revealed a concerning increase in T. indotineae with terbinafine resistance, including two novel isolates from China. Compared with T. interdigitale, T. mentagrophytes presented higher terbinafine MICs but similar azole susceptibility. Notably, 27 T. interdigitale isolates were classified as non-wild-type for terbinafine. Genetic diversity was analyzed for the SQLE, CYP51A and CYP51B gene. Specifically, T. indotineae isolates presented SQLE protein changes linked to terbinafine resistance. SQLE diversity was linked to terbinafine sensitivity, whereas alterations in CYP51A were associated with itraconazole sensitivity, with notable statistical significance evident across various protein isoforms. The relationship between protein diversity and drug sensitivity is presented in detail. Together, these findings highlight a growing prevalence of antibiotic resistance among Trichophyton and identify potential target genes for new therapies, underscoring the need for ongoing monitoring and offering directions for novel therapeutics.